Teaching Speaking through Story Telling: The Case of a Junior High School - Yelia Yelia; Vera Wahyuni; Rachmawati Rachmawati; Dony Efriza (Edukasi, 2021)
This collaborative classroom action research described the use of storytelling in teaching English speaking. The subjects of the research were 13 junior high school students at SMP Laboratorium STKIP Jambi, Indonesia. The qualitative data consisted of field notes, students’ diaries, photographs, and videos of teaching and learning process collected through observations and analyzed descriptively. The quantitative data were the students' scores in their English speaking performance generated through speaking tests and analyzed by using Microsoft Excel. The findings showed that the use of storytelling in teaching speaking could attract students’ attention to the lesson and encourage them to speak English. Pronouncing words, constructing sentences, and retelling the story could enhance students’ speaking performance. The students’ mean scores in their speaking performance tests got a significant improvement from cycle to cycle.